(untitled) (World Bulletin of Management and Law, 2024)
This thesis examines the significance of state policy regarding youth in the new Uzbekistan. It explores how the government’s initiatives and programs aimed at empowering and engaging young people have impacted societal development and progress in the country. The thesis delves into the key areas of focus in youth policy, such as education, employment, social participation, and cultural enrichment, highlighting the importance of investing in the younger generation for sustainable growth and prosperity in Uzbekistan.